Impact of Smart Health Wearables on Lifestyle - Sheetal Mahendher; Leonard L; Krithika G (Sumatera Medical Journal, 2026)
Background: Smart health monitoring wearables, including fitness trackers and smartwatches, are increasingly used to monitor physical activity, sleep, heart rate, stress, and health metrics. These devices provide continuous feedback that may influence users’ lifestyle choices. Objective: This study aimed to analyze the impact of smart health monitoring wearables on lifestyle choices and behaviors and assess users’ satisfaction with these devices. Methods: A survey-based study was conducted among a diverse group of individuals who use smart health monitoring wearables. Data were collected through a structured questionnaire assessing users’ experiences, lifestyle changes, perceived benefits, satisfaction, and limitations of wearable device use. Results: The findings showed that smart health monitoring wearables positively influenced users’ lifestyle choices. Participants reported greater motivation to exercise and maintain healthy sleep patterns. Real-time feedback encouraged healthier daily decisions, including choosing stairs instead of elevators and maintaining healthier eating habits. However, participants also identified limitations, including inaccurate measurements, limited medical relevance, data security concerns, over-reliance on devices, and limited battery life. Most users considered the benefits to outweigh the potential drawbacks. Conclusion: Smart health monitoring wearables can support healthier lifestyle choices through continuous monitoring and real-time feedback. Nevertheless, users should recognize their limitations and avoid relying on these devices as substitutes for medical assessment.